Updated checklist of the fireflies (Coleoptera: Lampyridae) of Mexico - Pérez-Hernández, Cisteil X.; Zaragoza-Caballero, Santiago; Romo-Galicia, Alberto (Zootaxa, 2022)
An updated checklist of fireflies (Coleoptera: Lampyridae) from Mexico is presented. The checklist includes the following valid taxa: the subfamilies Amydetinae Olivier in Wytsman, 1907, Chespiritoinae Ferreira, Keller and Branham, 2020, Photurinae Lacordaire, 1857, Pterotinae LeConte, 1861, and Lampyrinae Rafinesque, 1815, in addition to 8 tribes (including incertae sedis), 2 subtribes, 25 genera, and 232 species. We also propose Photinus cubilguitzi Pérez-Hernández & Zaragoza-Caballero nom. nov. as a replacement name for Photinus moestus (Gorham, 1884) nec Photinus moestus (Perty, 1830). At least 152 documented species (65.6% of the total) are restricted to Mexico, another 21 have also been recorded in Canada and the United States of America, and 59 in different Latin American countries. Remarkably, Photinini contains 64.6% (150 species) of the Mexican lampyrid fauna, and at least 54.7% (127 species) belong to the Photinus genus. The Mexican Transition Zone had higher Lampyridae species richness and endemism than the Nearctic and Neotropical biogeographic regions in the country, while the Transmexican Volcanic Belt, Veracruzan and Balsas Basin biogeographic provinces harbor the highest overall species richness and endemism. Veracruz and Oaxaca are the richest states in terms of lampyrid genera and species, while Aguascalientes, Querétaro and Zacatecas have only one or no species recorded each. To date, 10% of the global firefly fauna has been recorded in Mexico, and the country has a large number of endemic species. It is essential to intensify the study and fieldwork throughout the country to increase our knowledge of the group, with special focus on poorly explored regions and endemic species, and from other perspectives in addition to taxonomy.